Preliminary Assessment of Trace Metal Pollution and Their Bioaccumulation in Mollusks Inhabiting the Intertidal Sediments of the Atlantic Coast of Accra, Ghana - Emmanuel R. Blankson; Thyra F. Addison; Daniel Oduro; Juliet Ewool; Francis Gbogbo (Journal of Toxicology)
The present study investigated the trace metal levels in sediments, enrichment in sediments, and its bioaccumulation in mollusks collected from the intertidal sediments of the coast of Accra, Ghana, which is influenced by anthropogenic activities. The metals (Fe, Mn, Cu, Cr, and Zn) were analyzed in sediments. The metals (Mn, Cu, Cr, and Zn) were analyzed in the soft tissue of the mollusks collected from the different coastal areas. The results indicate that although Accra is the capital city and the coast receives tons of anthropogenic wastes, trace metal levels were low and there was no enrichment for the metals analyzed except Cu which showed minor to moderate enrichment in the coastal sediments. There was bioaccumulation of the trace metals in the soft tissue of the mollusks, and the results suggest that the mollusks studied, the gastropods (Agaronia razetoi) and the bivalves (Tivela tripla), can be used for biomonitoring.